5G Revolution: How Marketers Can Leverage the High-Speed Landscape - Suryani, Rani; Yuniasih, Idah; Aisyah, Nurul (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research examines the impact of 5G technology adoption on marketing success at PT. Leaden Indonesia, focusing on the role of marketing strategies adaptation in achieving success. Using a quantitative approach with random sampling, data were collected from a sample of 100 consumers, and Smart PLS was employed for analysis. The study's findings reveal that 5G Technology Adoption has a significant direct effect on Marketing Strategies Adaptation and Marketing Success. Additionally, the indirect effect of 5G Technology Adoption on Marketing Success through Marketing Strategies Adaptation is also significant, indicating that effective marketing adaptation is key to achieving marketing success. Similarly, while Speed and Connectivity does not have a significant direct effect on Marketing Success, it does show a significant indirect effect through Marketing Strategies Adaptation, suggesting that marketing success is closely linked to how well marketing strategies are adapted to leverage 5G's speed and connectivity. These results highlight the importance of flexibility and innovation in marketing strategy to capitalize on the benefits of 5G technology. The research concludes that for PT. Leaden Indonesia, successful marketing in a 5G environment depends on a robust adaptation of marketing strategies, emphasizing the need for companies to evolve their approaches to meet the changing demands of the market.